A Two-Point Perspective on Art: Multicultural-Nonsexist Education - Theresa E. McCormick (Educational Considerations, 1984)
Traditional art programs which have been chiefly concerned with the "old masters" in painting and drawing are no longer adequate for today's multicultural schools.